2016
DOI: 10.1017/s0950268816002004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of demographics on clinical outcome of dengue: a cross-sectional study of 6703 confirmed cases in Vitória, Espírito Santo State, Brazil

Abstract: SUMMARYDengue presents a wide clinical spectrum of signs and symptoms, with characteristics of the host potentially influencing the disease evolution. Therefore, the purpose of this study was to evaluate the influence of gender and age on dengue clinical outcomes in a recent outbreak situation in Brazil, applying a cross-sectional design and including 6703 dengue cases with laboratory confirmation, occurring in Vitória, Espírito Santo State, Brazil, between 2007 and 2013. Data were obtained from the Informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
(57 reference statements)
0
15
0
1
Order By: Relevance
“…Acute renal failure also occurred in higher frequency in individuals aged 65 and above with DHF as compared to those under 65 years of age (12.1% vs. 1.7%, P = 0.001) [33]. However, no significant difference in the prevalence of neurological and cardiac manifestations of dengue has been observed thus far [32].…”
Section: Severe Dengue and Complicationsmentioning
confidence: 90%
See 4 more Smart Citations
“…Acute renal failure also occurred in higher frequency in individuals aged 65 and above with DHF as compared to those under 65 years of age (12.1% vs. 1.7%, P = 0.001) [33]. However, no significant difference in the prevalence of neurological and cardiac manifestations of dengue has been observed thus far [32].…”
Section: Severe Dengue and Complicationsmentioning
confidence: 90%
“…Similarly, a large cross-sectional study of 6703 laboratory-confirmed cases of dengue in Vitória, Brazil, demonstrated that elderly adults, aged 60-88 years, had an adjusted odds ratio of 1.56 (1.23-1.99, 95% CI) as compared to younger adults, aged 20-59 years, of having severe dengue [32].…”
Section: Severe Dengue and Complicationsmentioning
confidence: 95%
See 3 more Smart Citations